Measuring the impact of social programs in Laznas Al-Azhar village empowerment programs using the Social Return On Investment (SROI) and Sustainable Livelihood Impact Analysis (SLIA) methods (case study of Puncu Village, Kediri, East Java) - Nugroho, Agung; Habibah, Rini Yaumi; Rosidin, Fatchuri; Sidik, Rahmatullah; Salim, Deden Nurdin (2023)
Starting from the eruption of Mount Kelud in Kediri in 2014, LAZ Al Azhar was present to provide disaster response with a program called FORMULA (Food, Religion, Medic and Livelihood Aid). As the post-disaster recovery process progresses, LAZ Al Azhar has rebuilt the infrastructure and economy of the village community by carrying out a village assistance program called "Desa Gemilang". This program, which has been running for seven years, has positively impacted the development and progress of village communities. The impact assessment methods used in this research are Social Return on Investment (SROI) and Sustainable Livelihood Impact Analysis (SLIA). The result of calculating the final value of the program impact study using the SROI method is 1.51, which means that for every investment of IDR 1,- get a benefit of IDR 1.51. With this value, in terms of social investment, the Puncu Village empowerment program is in the successful category. Furthermore, the program impact study results using the SLIA method provide change values for 5 assets, namely natural, physical, human, financial, and social capital. The change value consists of 3.94% (natural capital), 30.60% (physical capital), 30.61% (human capital), 30.27% (financial capital), and 21.74% (social capital). The results of this research also provide recommendations for strengthening the program.